2022
DOI: 10.1021/acsomega.2c02121
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Debinding Kinetics of Gelcast Ceramic Parts via a Modified Independent Parallel Reaction Model in Comparison with the Multiple Normally Distributed Activation Energy Model

Abstract: This work aims to provide useful insights into the thermal debinding kinetics of gelcast ceramic parts, especially for debinding kinetics prediction involving heat preservation. Debinding experiments were conducted in a differential thermogravimetric analyzer at five heating rates (5, 8, 10, 15, and 20 °C/min) in the temperature range of 35–900 °C under an air atmosphere. The conversion (α) and pyrolysis rate (dα/d T ) data were simulated using a modified independent parallel reaction (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 40 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…In addition, it was found that a thermal hysteresis appeared in the DTG curve as the heating rate increased. The peak value of the DTG curves increased and shifted to the high-temperature region, due to the different conversion rates of petroleum coke at different heating rates …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, it was found that a thermal hysteresis appeared in the DTG curve as the heating rate increased. The peak value of the DTG curves increased and shifted to the high-temperature region, due to the different conversion rates of petroleum coke at different heating rates …”
Section: Resultsmentioning
confidence: 99%
“…The IPR model has been widely used in pyrolysis fields such as biomass and industrial waste, and relevant studies reported that model predictions agreed well with the experimental data. The IPR model, also known as the n -pseudocomponent model, means that the pyrolysis process of petroleum coke can be described by several independent parallel first or n th reactions, each of which corresponds to the pyrolysis of different components in petroleum coke. This can be described as follows normald ( m t / m 0 ) normald t = prefix− prefix∑ c i · normald α i normald t goodbreak0em1em⁣ i = 1 , 2 , 3 , ... N normald α i normald t = k i · exp ( E i R · T ) · false( 1 α i false) n i where subscript i represents the i th pseudocomponent, and c i is the mass fraction of pseudocomponent i .…”
Section: Materials and Methodologymentioning
confidence: 99%
See 3 more Smart Citations